Author Correction: Clinical Manifestations and Ophthalmic Outcomes of Ocular Syphilis at a Time of Re-Emergence of the Systemic Infection - Furtado, João M.; Arantes, Tiago E.; Nascimento, Heloisa; Vasconcelos-Santos, Daniel V.; Nogueira, Natalia; Queiroz, Rafael de Pinho; Brandão, Luana P.; Bastos, Thaís; Martinelli, Ricardo; Santana, Rodrigo C.; Muccioli, Cristina; Belfort, Rubens; et al. (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.